Biophysical studies on enzymes related to antibiotics - Kamps, JJAG (2020)
The work described in this thesis concerns two research areas: (i) time resolved (tr) crystallography studies on two enzymes, oxacillinase 10 (OXA-10) and isopenicillin N synthase (IPNS); and (ii) the reactivity of formaldehyde towards amino acids. OXA-10 is a class D serine β-lactamase that confers bacterial resistance against clinically relevant β-lactam antibiotics. IPNS is a non-heme Fe dependent enzyme that catalyses the formation of isopenicillin N (IPN) from L-δ-(α-aminoadipoyl)-L-cysteinyl D-valine (ACV), which is an important step in the biosynthesis of penicillins and cephalosporins. Formaldehyde is an environmental pollutant and a metabolite in many biochemical reactions. Formaldehyde is toxic and considered carcinogenic above threshold levels, however its reactivity with biomolecules is not well defined.